2018
DOI: 10.3847/1538-4357/aadb93
|View full text |Cite
|
Sign up to set email alerts
|

Possible Counterrotation between the Disk and Protostellar Envelope around the Class I Protostar IRAS 04169+2702

Abstract: We present results from our SMA observations and data analyses of the SMA archival data of the Class I protostar IRAS 04169+2702. The high-resolution (∼0. 5) 13 CO (3-2) image cube shows a compact (r 100 au) structure with a northwest (blue) to southeast (red) velocity gradient, centered on the 0.9-mm dust-continuum emission. The direction of the velocity gradient is orthogonal to the axis of the molecular outflow as seen in the SMA 12 CO (2-1) data. A similar gas component is seen in the SO (6 5 -5 4 ) line. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 66 publications
3
11
0
Order By: Relevance
“…On the other hand, the velocity gradient map in K04169 appears to be rather complex and displays two converging flows, from the northeast and the southwest (Figure 3(b)). Counterrotation between the disk and the envelope in K04169 is also reported (Takakuwa et al 2018). We see that the core mean B-field (q B core, ∼121°) is nearly aligned parallel to the mean orientation of the velocity gradient (θ G ∼126°; see Table 2).…”
Section: K04166 and K04169supporting
confidence: 69%
See 1 more Smart Citation
“…On the other hand, the velocity gradient map in K04169 appears to be rather complex and displays two converging flows, from the northeast and the southwest (Figure 3(b)). Counterrotation between the disk and the envelope in K04169 is also reported (Takakuwa et al 2018). We see that the core mean B-field (q B core, ∼121°) is nearly aligned parallel to the mean orientation of the velocity gradient (θ G ∼126°; see Table 2).…”
Section: K04166 and K04169supporting
confidence: 69%
“…It is fragmented into a chain of cores that are in the early evolutionary stages of low-mass star formation (Figure 1(b)). These include three prestellar cores, namely, Miz-8b, Miz-2, and HGBS-1 (Mizuno et al 1994;Marsh et al 2016); two class 0/I protostellar cores, IRAS 04166+2706 and IRAS 04169+2702 (Ohashi et al 1997;Tafalla et al 2010;Takakuwa et al 2018); and one evolved object, J04194148+2716070, classified as a class II T Tauri star (Davis et al 2010). We hereafter refer to IRAS 04166+2706 and IRAS 04169+2702 as K01466 and K04169, respectively (see Kenyon et al 1990Kenyon et al , 1993, adopting the core nomenclature of Bracco et al (2017).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that the arclike structure of infalling envelopes may be naturally formed by the turbulent accretion of the infalling matter in the early phase of YSOs. Takakuwa et al (2018) found a Class I YSO in which the rotation direction of the circumstellar envelope significantly change from 1000 au scale to inner 100 au scale, which can be interpreted as a counter rotation between the protoplanetary disk and circumstellar envelope. The physical mechanism which induces such a counter-rotating structure is still unclear.…”
Section: Warped Disksmentioning
confidence: 96%
“…Recent observations of protostellar systems have shown more detailed and complicated disk and envelope structures. The Class I protostar IRAS 04169+2702 shows a velocity structure, implying that its envelope rotates in the opposite direction to its disk (Takakuwa et al 2018), which could be explained by the Hall effect, one of non-ideal MHD effects (Tsukamoto et al 2015(Tsukamoto et al , 2017. IRS 43, which is a binary system in the Ophiuchus molecular cloud, has two misaligned circumstellar disks with a circumbinary disk (Brinch et al 2016).…”
Section: Introductionmentioning
confidence: 99%